Chame Ibérique et Prébétique. Troisiéme jour. - Foucault, A.; Fourcade, E.; Alonso, A.; Arias, C.; Azema, J.; Vilas, Lorenzo; García Quintana, Álvaro; Mas, J.R. (Cuadernos de Geología Ibérica, 1979)
Sin resumen